A local criterion of fairness in sport: Comparing the property advantages of Caster Semenya and Eero Mäntyranta with implications for the construction of categories in sport - Camporesi, Silvia (Bioethics, 2021)
This paper aims to bring a novel approach to the discussion of unfair advantages in sport by looking for a local criterion of fairness instead of a universal criterion. A local criterion of fairness would not solve the general dispute over what counts as an unfair advantage, but it would be beneficial in evaluating specific cases and could guide further discussion about them. We seek a local criterion of fairness by comparing the specific property advantages of Caster Semenya and Eero Mäntyranta. South African Semenya is a middle-distance runner whose right to compete in the female category has been challenged owing to her assumed difference of sex development and related high level of testosterone. Finnish Mäntyranta was a cross-country skier with an exceptionally high haematocrit level. We examine whether there is a relevant difference between their advantages that would justify treating the athletes differently. We propose that the criterion ‘not attainable by other athletes in the same category’ could stand as a local criterion of fairness under certain conditions. However, its proper application requires further discussion on how to justify categories in sport.